Do Fixed-Term Contracts Increase the Long-Term Employment Opportunities of the Unemployed? - Tobias Hagen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
The paper investigates whether (unsubsidised) fixed-term contracts (FTCs) are a means of integration for the unemployed in the West German labour market. This is done by analysing whether entering into an FTC improves the employment opportunities of an unemployed person in terms of the probability of subsequent permanent contracts and subsequent periods of employment and unemployment. The empirical analysis is based on propensity score matching methods, obtaining the effects of FTCs by comparing the future situation of (?treated?) unemployed entering into FTCs after a particular unemployment duration with a suitable control group of ?non-treated? individuals. In principal different counterfactual situations for treated persons entering into FTCs after a certain number of month of unemployment are reasonable. A first counterfactual is never to enter into an FTC. A second counterfactual is not to take up an FTC job in this month but possibly in a later month. These two possible counterfactuals imply different definitions for the group of non-treated individuals and impose different policy questions. Both definitions are analysed in the paper. The propensity score is estimated by a discrete hazard rate model, which seems to be an appropriate way of taking into account the potential endogenous effect of the unemployment duration on the selection into the type of contract. Further insights are gained by comparing the determinants of the transition to FTC and permanent contract jobs. There is some evidence that FTCs may serve as ?stepping stones? towards permanent employment for the unemployed. However, the hypothesis that FTCs lead to dual labour markets cannot be rejected.
Keywords: C14; C41; J41; J64; 330; Fixed-term Contracts; Propensity Score Matching; Hazard Rate Model; Unemployment Duration; Stepping Stones; Dual Labour Markets; Befristeter Arbeitsvertrag; Arbeitslosigkeit; Dauer; Betriebszugehörigkeit; Schätzung; Deutschland